2021
DOI: 10.1186/s42826-021-00108-x
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-induced lung-injury in mouse models: Is there a trap?

Abstract: Ventilator-induced lung injury (VILI) is a serious acute injury to the lung tissue that can develop during mechanical ventilation of patients. Due to the mechanical strain of ventilation, damage can occur in the bronchiolar and alveolar epithelium resulting in a cascade of events that may be fatal to the patients. Patients requiring mechanical ventilation are often critically ill, which limits the possibility of obtaining patient samples, making VILI research challenging. In vitro models are very important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 117 publications
0
11
0
Order By: Relevance
“…Mouse models of VILI have shown that overstretching the lung tissues increases the inflammatory response in mice along with damaging the lung epithelium [ 3 ]. Setting up our own mouse model of VILI, we set out to identify important genes involved in the transcriptional response to mechanical ventilation of different tidal volumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouse models of VILI have shown that overstretching the lung tissues increases the inflammatory response in mice along with damaging the lung epithelium [ 3 ]. Setting up our own mouse model of VILI, we set out to identify important genes involved in the transcriptional response to mechanical ventilation of different tidal volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The four main hallmarks of VILI have traditionally been baro/volutrauma, atelectrauma, oxygen toxicity and biotrauma [ 3 ]. Baro/volutrauma occurs when using inappropriately high airway pressures or tidal volumes subjecting open alveoli to over-distension.…”
Section: Introductionmentioning
confidence: 99%
“…This must be considered in the selection of a mouse ARDS model. As shown in Table 1 , models directly linked to lung damage use intratracheal or intranasal application of lipopolysaccharide (LPS) or bacteria, intratracheal instillation of acids or bleomycin, 100% O 2 and mechanical ventilation (MV) [ 18 ], or pulmonary ischemia/reperfusion injury. Whereas the last-mentioned intervention requires surgery, all the other methods depend on intranasal or intratracheal application, which is easier to achieve.…”
Section: Methodsmentioning
confidence: 99%
“…The EIT measurement was undertaken during the following ventilator maneuver: An initial respiratory rate set at 120 breaths/min and positive end-expiratory pressure of 5 cm H 2 O ( Basoalto, et al, 2021 ; Ferrini, et al, 2021 ; Joelsson et al, 2021 ). Over 120 s, PIP was increased from 10 to 35 cm H 2 O in 5 cm H 2 O increments (stepwise inflation) and thereafter returned in 5 cm H 2 O steps back to the baseline (stepwise deflation).…”
Section: Methodsmentioning
confidence: 99%